Pelayanan Pendidikan Keagamaan Komunitas Muslim Minoritas di Bali - Ta'rif Ta'rif (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
This article depicts the implementation of religious educational service in minority society-involving the form and kinds of religious educational service given by minority society, the obstacles of its establishment and also its expectation to religious education in minority society. By taking a case in Tabanan, it is found that religious educational service in the region can’t be aparted from participation of Moslem minority, All minority muslim society has been serve, since teenager to adult. Though in the limited equipment and the low prospevity of teachers, the muslim is still learn Islam in high spirit.